Metodologi Penelitian Derajat Kepublikan Ruang Terbuka Publik Perkotaan - Fath Nadizti; Himasari Hanan (Archvisual: Jurnal Arsitektur dan Perencanaan, 2022)
The degree of publicness is an approach to assessing the extent to which an open space is public. This approach has grown rapidly over the last twenty years, particularly in Europe and the United States. This article describes the dynamics and development of publicity research through a literature review. Eight scientific journals and one book were qualitatively reviewed using the content analysis method. This article finds that the key to the degree of publicity is adjusting the indicators to the context of the place and culture of an urban open space. In Indonesia, the cultural context of the city development process and local characteristics are two important things in the application of the degree of publicity approach.